Numerical simulation on the effect of anastomosis and stenosis upon radiocephalic arteriovenous fistula - Wan Anuar, Wan Hassan (2014)
In the present study, the hemodynamic effect of variations of anastomosis angle and length and stenosis were investigated on several parameters such as pressure drop and wall shear stress. A total of 36 three-dimensional, simplified models of side-to-end radiocephalic arteriovenous fistula (RCAVF) were used to analyse the hemodynamic effect of anastomosis angle and length and other 21 models were used to analyse the hemodynamic effect of stenosis under average systolic and diastolic arterial and venous pressure. The flows in the models were simulated using EFD Lab software solving the Navier-Stokes equation with steady flow conditions. The results showed that high pressure drop over the anastomosis were observed for RCAVF with smaller anastomosis angle and length and for RCAVF with larger percentage of stenosis. Results also showed that the pressure drop over the anastomosis decreased significantly for the case of anastomosis angle less than 30o and anastomosis length less than 6 mm. For cases with anastomosis angle larger than 45o, the pressure drop decreased slightly and became relatively constant. For anastomosis length, the pressure drop decreased slightly for anastomosis length of 5 mm to 10 mm and stabilized for anastomosis length of 8 mm to 10 mm. The analysis showed that the size of stenosis larger than 63% for Type 1, 48% for Type 2 and 63% for Type 3 tends to progress. Full progression of these stenoses results in the formation of blood clot or thrombosis, thus affecting the function of RCAVF. Therefore, it is recommended that the anastomosis angle should be considered between 30o to 60o (around 45o) and the anastomosis length should be maintained between 7 mm and 8 mm to minimize adverse effects. It is also suggested that Type 1, Type 2 and Type 3 stenosis should be treated early before they narrow to 63%, 48% and 63%, respectively, due to the progression of these stenoses